Dressed, undressed, or both; The case of Ewaw in Southeast Maluku - van Engelenhoven, Aone (UI Scholars Hub, 2021)
This article discusses complexity and simplification in Ewaw (also known as Kei or Keiese), an Austronesian language in Southeast Maluku. Section 1 provides an introduction to the genetics, spelling, and phonology of this language, which is related to the Austronesian languages of Timor. There are two main dialects which subdivide into two variants each. Section 2 provides an overview of the productive inflection in Ewaw and its derivational morphology, of which only reduplication is still productive. It has two noun classes and four verb classes, seventeen derivational prefixes and four derivational suffixes. Section 3 is a sketch of Ewaw syntax and deixis. It has twenty-four adverbial markers to encode direction and manner, which can all be analysed as serial verb constructions. Section 4 compares Ewaw grammar to languages in the region. Whereas Ewaw's petrified morphology is more complex than in any other language in the region, it now has the simplest morphology. Section 5 concludes that Ewaw's simplification without